Apert syndrome: A consensus on the management of Apert hands. Issue 2 (February 2017) - Pettitt, David A.; Arshad, Zeeshaan; Mishra, Anuj; McArthur, Paul
Abstract: Introduction: Apert Syndrome is a congenital condition characterised by primary craniosynostosis, midfacial malformations and complex symmetrical malformations of the hands and feet. The hands demonstrate one of the most complex collections of congenital upper limb deformities, posing a significant challenge for the paediatric hand surgeon. This study examines the extant literature and current practice of the four UK specialist craniofacial units regarding the management of Apert hands in order to provide a basis for guideline development. Methods: The current literature was reviewed. Survey-type questionnaires were distributed to the four UK specialist craniofacial units and responses analysed. Results: Management of the Apert hand is largely dictated by the degree of malformation present. Although all units aim to achieve a five digit hand, variation in the timing of surgery, operative protocols and mobilisation policies exist. Conclusion: The results of this study provide an interesting snapshot of the current management of Apert hands across four UK craniofacial surgery units. The four UK units remain congruent on most areas surrounding the management of Apert hands although some minor inter-unit variation exists. A multidisciplinary approach to management remains fundamental in optimising the regain of function and aesthetically acceptable hands.